Ethics of access to newly approved expensive medical treatments: multi-stakeholder dialogues in a publicly funded healthcare system - Bomhof, Charlotte H. C.; Smids, Jilles; Sybesma, Sybren; Schermer, Maartje; Bunnik, Eline M. (Frontiers in Pharmacology, 2024)
Background: Due to rising healthcare expenditures, countries with publicly funded healthcare systems face challenges when providing newly approved expensive anti-cancer treatments to all eligible patients. In the Netherlands in 2015, the so-called Coverage Lock (CL), was introduced to help safeguarding the sustainability of the healthcare system. Since then, newly approved treatments are no longer automatically reimbursed. Previous work has shown that as policies for access to CL treatments are lacking, patient access to non-reimbursed treatments is limited and variable, which raises ethical issues. The ethics of access were discussed in a series of multi-stakeholder dialogues in the Netherlands. Methods: Three dialogues were held in early 2023 and included physicians, health insurers, hospital executives, policy makers, patients, citizens, and representatives of pharmaceutical companies, patient and professional organizations. In advance, participants had received an ‘argument scheme’ featuring three models: 1) access based on third-party payment (e.g. by pharmaceutical companies, health insurers or hospitals) 2) access based on out-of-pocket payments by patients 3) no access to CL treatments. During the dialogues, participants were asked to discuss the merits of the ethical arguments for and against these models together, and ultimately to weigh them . The discussions were audio-taped, transcribed, coded, and thematically analyzed. Results: Generally, most stakeholders were in favour of allowing access – at least when treatments are clearly beneficial – to treatments in the CL. When discussing third-party payment, stakeholders favoured payment by pharmaceutical companies over payment by health insurers or hospitals, not wanting to usurp collective funds while cost-effectiveness assessments are still pending. Largely, stakeholders were not in favour of out-of-pocket payments, emphasizing solidarity and equal access. Recurrent themes included the conflict between individual and collective interests, shifting attitudes, withholding access to put pressure on the system and the importance of transparency about access to CL-treatments Conclusion: Policies for access to non-reimbursed treatments should address stakeholders’ concerns regarding transparency, equal access and solidarity, and loss of potential health benefits for patients. Multi-stakeholder dialogues are an important tool to help inform policy-making on access to newly approved, (too) expensive treatments in countries facing challenges to the sustainability of healthcare systems.